2005
DOI: 10.1186/bcr1260
|View full text |Cite
|
Sign up to set email alerts
|

Greatly increased occurrence of breast cancers in areas of mammographically dense tissue

Abstract: IntroductionMammographic density is a strong, independent risk factor for breast cancer. A critical unanswered question is whether cancers tend to arise in mammographically dense tissue (i.e. are densities directly related to risk or are they simply a marker of risk). This question cannot be addressed by studying invasive tumors because they manifest as densities and cannot be confidently differentiated from the densities representing fibrous and glandular tissue. We addressed this question by studying ductal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(133 citation statements)
references
References 12 publications
3
130
0
Order By: Relevance
“…Percent mammographic density reflects relative amounts of fibroglandular and fat tissue, and absolute mammographic density reflects epithelial and stromal tissues, the dense areas of the breast (14,15). Importantly, there is a clear tendency for ductal carcinoma in situ, and invasive breast cancer to occur in areas that are mammographically dense (16). Of note, absolute mammographic density, as compared with percent mammographic density, may be less confounded by body fat (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Percent mammographic density reflects relative amounts of fibroglandular and fat tissue, and absolute mammographic density reflects epithelial and stromal tissues, the dense areas of the breast (14,15). Importantly, there is a clear tendency for ductal carcinoma in situ, and invasive breast cancer to occur in areas that are mammographically dense (16). Of note, absolute mammographic density, as compared with percent mammographic density, may be less confounded by body fat (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…When women from countries with a low BCa incidence, such as many Asian countries, miEffects of a Low-Fat, High-Fiber Diet and Exercise Program on Breast Cancer Risk Factors In Vivo and Tumor CelI Growth and Apoptosis In Vitro R. James Barnard, Jenny Hong Gonzalez, Maud E. Liva, and Tung H. Ngo grate to countries such as the United States and adopt a Western lifestyle, the incidence ofBCabecomes equal tothat found in the host country (5). BCa is also on the rise in Asian countries as they adopt a Western lifestyle (6). Four lifestyle factors that have received much attention are obesity, diet, physical activity, and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, high mammographic density throughout the breast may account for up to 30% of breast cancers, whereas mutations in BRCA1 or BRCA2 -although conferring a greater relative risk -account for only 5% of total breast cancers [see Boyd et al (Boyd et al, 2005) and references therein]. Furthermore, a recent study revealed that ductal carcinoma in situ occurs overwhelmingly in dense regions of the breast (Ursin et al, 2005), suggesting that local densities in breast tissue increase cancer risk.Importantly, regions of increased breast density have substantially increased deposition of fibrillar collagen and collagenassociated proteoglycans such as decorin (Alowami et al, 2003;Guo et al, 2001;Li et al, 2005). Until recently, the link between mammographically dense breast tissue and the composition of breast tissue had only been correlative, as there was no direct evidence for a causative link.…”
mentioning
confidence: 99%